COMPANIES’ INTEREST IN ENTERPRISE SOCIAL NETWORKS IN THE CZECH REPUBLIC - Školudová, Jana (European Scientific Journal, ESJ, 2015)
To a degree, the development of organizations in the current competitive environment of an information society depends on the abilities to share and use employees’ knowledge on all business levels better and faster than the competition. Findings from international studies and research that have been conducted show that enterprise social networks can provide a range of advantages for modern human resource management. The reasons mentioned reveal the necessity of primarily determining interest in using the enterprise social network in the Czech Republic. A poll was conducted on the basis of intentional non-random choice, and research questions were posed to company managers. An overall comparison of the data gathered indicates two main resulting tendencies and point to an incipient trend in the Czech Republic.